1998
DOI: 10.1046/j.1365-2427.1998.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

In situ experiments on predatory regulation of a bivalve mollusc (Dreissena polymorpha) in the Mississippi and Ohio Rivers

Abstract: 1. In situ exclosure experiments in the Mississippi and Ohio Rivers determined the importance of fish predation in regulating zebra mussels (Dreissena polymorpha), an increasingly important constituent of the benthic invertebrate assemblages in both rivers. 2. We evaluated the effects of predatory fish on the density, biomass and size distribution of zebra mussels in a floodplain reach of the upper Mississippi River and in a naturally constrained reach of the Ohio River. Fifty, six‐sided, predator‐exclusion ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 26 publications
3
69
0
Order By: Relevance
“…Similarly, previous investigations on fish predation in areas without the round goby showed negative effects on Dreissena density (Thorp et al 1998;Bartsch et al 2005). In our experiment, round goby growth rates were negatively associated with initial stocking biomass in enclosures (Figure 2), suggesting that food was a limiting resource in cages.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Similarly, previous investigations on fish predation in areas without the round goby showed negative effects on Dreissena density (Thorp et al 1998;Bartsch et al 2005). In our experiment, round goby growth rates were negatively associated with initial stocking biomass in enclosures (Figure 2), suggesting that food was a limiting resource in cages.…”
Section: Discussionsupporting
confidence: 71%
“…There are several fishes in Muskegon Lake Bhagat and Ruetz 2011) that have been known to eat Dreissena such as the freshwater drum (Aplodinotus grunniens), pumpkinseed (Lepomis gibbosus), redhorse suckers (Moxostoma spp. ), and common carp (Cyprinus carpio) (Tucker et al 1996;Thorp et al 1998;Magoulick and Lewis 2002;Andraso 2005;Bartsch et al 2005). Large-bodied molluscivorous fishes were implicated in limiting Dreissena densities in a Lake Erie costal wetland (Bowers and de Szalay 2007) and in the Upper Mississippi River (Bartsch et al 2005), although there was spatial variation in the magnitude of the effect in the Upper Mississippi River.…”
Section: Discussionmentioning
confidence: 99%
“…Physicochemical properties of the recipient environment, such as surface area, depth, substrate, Ca concentration, pH, temperature, and trophic status, have been suggested as main factors constraining density, growth, and invasion success of zebra mussels at regional (among-lake) scales (Ramcharan et al 1992b, Mellina and Rasmussen 1994, Sprung 1995, Naddafi 2007, Whittier et al 2008, whereas biotic factors, such as fish predation, have been suggested as secondary factors (Thorp et al 1998). McMahon (1991) proposed fishes as the most active predators of settled zebra mussels, but only a handful of studies have indicated the potential of fish predation to control invasion success and density of exotic mussels (Eggleton et al 2004, Bartsch et al 2005, Watzin et al 2008.…”
mentioning
confidence: 99%
“…McMahon (1996 proposed fishes as the most active predators of settled zebra mussels, but only a handful of studies have indicated the potential of fish predation to control the invasion success and density of exotic mussels (Eggleton et al 2004;Bartsch et al 2005;Watzin et al 2008). The results of Magoulick and Lewis (2002) indicate that predation could potentially suppress initial zebra mussel colonization and recolonization of adult zebra mussels following temperature-dependent mortality, and the relative susceptibility of zebra mussels to predation can be influenced for several biological and ecological factors (Thorp et al 1998). Perry et al (2000) and Naddaffi et al (2010) also suggested the potential impacts of predation on recruitment or on the early life history stages of zebra mussels, because during the early stages of an invasion the average zebra mussel size is small and these individuals are therefore more vulnerable.…”
Section: Introductionmentioning
confidence: 99%